Low Tunneling Decay of Iodine-Terminated Alkane Single-Molecule Junctions - Lin-Lu Peng; Bing Huang; Qi Zou; Ze-Wen Hong; Ju-Fang Zheng; Yong Shao; Zhen-Jiang Niu; Xiao-Shun Zhou; Hu-Jun Xie; Wenbo Chen (Nanoscale Research Letters, 2018)
Abstract One key issue for the development of molecular electronic devices is to understand the electron transport of single-molecule junctions. In this work, we explore the electron transport of iodine-terminated alkane single molecular junctions using the scanning tunneling microscope-based break junction approach. The result shows that the conductance decreases exponentially with the increase of molecular length with a decay constant β N = 0.5 per –CH2 (or 4 nm−1). Importantly, the tunneling decay of those molecular junctions is much lower than that of alkane molecules with thiol, amine, and carboxylic acid as the anchoring groups and even comparable to that of the conjugated oligophenyl molecules. The low tunneling decay is attributed to the small barrier height between iodine-terminated alkane molecule and Au, which is well supported by DFT calculations. The work suggests that the tunneling decay can be effectively tuned by the anchoring group, which may guide the manufacturing of molecular wires.